High energy white beam x-ray diffraction studies of residual strains in engineering components - Zhang, S; Vorster, W; Jun, T; Song, X; Golshan, M; Laundy, D; Walsh, M; Korsunsky, A (American Institute of Physics, 2008)
In order to predict the durability of engineering components and improve performance, it is mandatory to understand residual stresses. The last decade has witnessed a significant increase of residual stress evaluation using diffraction of penetrating radiation, such as neutrons or high energy X-rays. They provide a powerful non-destructive method for determining the level of residual stresses in engineering components through precise characterisation of interplanar crystal lattice spacing. The unique non-destructive nature of these measurement techniques is particularly beneficial in the context of engineering design, since it allows the evaluation of a variety of structural and deformational parameters inside real components without material removal, or at worst with minimal interference. However, while most real engineering components have complex shape and are often large in size, leading to measurement and interpretation difficulties, since experimental facilities usually have limited space for mounting the sample, limited sample travel range, limited loading capacity of the sample positioning system, etc. Consequently, samples often have to be sectioned, requiring appropriate corrections on measured data; or facilities must be improved. Our research group has contributed to the development of engineering applications of high-energy X-ray diffraction methods for residual stress evaluation, both at synchrotron sources and in the lab setting, including multiple detector setup, large engineering component manipulation and measurement at the UK Synchrotron Radiation Source (SRS Daresbury), and in our lab at Oxford. A nickel base superalloy combustion casing and a large MIG welded A1 alloy plate were successfully studied.